Body Balance and Physiotherapy in the Aquatic Environment and at a Gym. (22nd June 2021) - Pieniążek, Magdalena; Mańko, Grzegorz; Spieszny, Michał; Bilski, Jan; Kurzydło, Wojciech; Ambroży, Tadeusz; Jaszczur-Nowicki, Jarosław
Abstract : The increase in the average age of our society represents a growing medical and social problem, which requires concentration on the issue concerning balance disorders. The aquatic environment has a number of complex properties that have miscellaneous effects on the human body. In the light of the above, water is becoming an ideal environment to learn correct neuromuscular communication, and a properly prepared training session in water helps to practice balance and movement coordination. The objective of the study was to assess the impact of rehabilitation in the aquatic environment on patients' balance and compare the results obtained with patients who received rehabilitation at a gym. The study was carried out among patients hospitalised in the "Krzeszowice" Rehabilitation Centre. It encompassed 137 patients, randomly assigned to either the study group (the aquatic environment) or the control group (the gym). The preliminary examination included general medical history and a test on the stabilometric platform. The patients attended training sessions for 4 weeks, 5 times a week for 30 minutes. It was a single-blinded study wherein the authors did not know which group a given patient had been assigned to. Upon completion of a monthly therapy, the stabilometric test was carried out again. The study revealed that the patients from both groups experienced a significant improvement in balance. However, the improvement was slightly greater in those exercising in the pool. Physiotherapy in the aquatic environment makes a greater contribution to the improvement of body balance compared to physical exercises performed at a gym.